Multipotent glia-like stem cells mediate stress adaptation - Rubin de Celis, Maria F.; Garcia-Martin, Ruben; Wittig, Dierk; Valencia, Gabriela D.; Enikolopov, Grigori; Funk, Richard H.; Chavakis, Triantafyllos; Bornstein, Stefan R.; Androutsellis-Theotokis, Andreas; Ehrhart-Bornstein, Monika (AlphaMed Press, 2015)
The neural crest-derived adrenal medulla is closely related to the sympathetic nervous system; however, unlike neural tissue, it is characterized by high plasticity which suggests the involvement of stem cells. Here, we show that a defined pool of glia-like nestin–expressing progenitor cells in the adult adrenal medulla contributes to this plasticity. These glia-like cells have features of adrenomedullary sustentacular cells, are multipotent, and are able to differentiate into chromaffin cells and neurons. The adrenal is central to the body’s response to stress making its proper adaptation critical to maintaining homeostasis. Our results from stress experiments in vivo show the activation and differentiation of these progenitors into new chromaffin cells. In summary, we demonstrate the involvement of a new glia-like multipotent stem cell population in adrenal tissue adaptation. Our data also suggest the contribution of stem and progenitor cells in the adaptation of neuroendocrine tissue function in general.